2021
DOI: 10.3390/toxins13120912
|View full text |Cite
|
Sign up to set email alerts
|

PKCζ-Mitogen-Activated Protein Kinase Signaling Mediates Crotalphine-Induced Antinociception

Abstract: Crotalphine (CRP) is a structural analogue to a peptide that was first identified in the crude venom from the South American rattlesnake Crotalus durissus terrificus. This peptide induces a potent and long-lasting antinociceptive effect that is mediated by the activation of peripheral opioid receptors. The opioid receptor activation regulates a variety of intracellular signaling, including the mitogen-activated protein kinase (MAPK) pathway. Using primary cultures of sensory neurons, it was demonstrated that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, it is suggested that the microglial p38 mitogen-activated protein kinase (p38-MAPK) pathway is involved in the β-endorphin release and that minocycline prevented this release attenuating p38 activation [ 45 , 46 ]. Interestingly, our group has previously demonstrated that crotalphine increases the activation of spinal MAPK and that its analgesic effect is dependent on the activation of ERK1/2 and JNK MAPK via the PKCζ signaling pathway [ 24 ]. Therefore, we can suggest that the effect of crotalphine on spinal microglial cells is a key step for antinociceptive effect, through the release of endogenous opioid peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is suggested that the microglial p38 mitogen-activated protein kinase (p38-MAPK) pathway is involved in the β-endorphin release and that minocycline prevented this release attenuating p38 activation [ 45 , 46 ]. Interestingly, our group has previously demonstrated that crotalphine increases the activation of spinal MAPK and that its analgesic effect is dependent on the activation of ERK1/2 and JNK MAPK via the PKCζ signaling pathway [ 24 ]. Therefore, we can suggest that the effect of crotalphine on spinal microglial cells is a key step for antinociceptive effect, through the release of endogenous opioid peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, crotalphine does not induce side effects commonly observed for opioids or other analgesic drugs, such as tolerance (even after chronic administration—every 3 days for 75 days), or alteration in general and spontaneous motor activity [ 20 ]. Crotalphine does not interfere with the viability of DRG cells [ 24 ] or of human sensory-like neurons SH-SY5Y (data not published) and does not interfere with the body weight of rodents [ 25 ]. However, no study has yet investigated crotalphine effects on the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Venoms from other animals are also reported; the venoms of centipedes [10], scorpions [11,12], fishes [13,14], and caterpillars [15], including microbial toxins [16]. The great potential for molecules derived from animal venoms as drug leads was also reviewed [17], and the antimicrobial [18], anticoagulant [19,20], and analgesic [21,22] effects have been highlighted in original studies reported here.…”
mentioning
confidence: 95%